PROLIFERATION AND APOPTOSIS OF B-CELL LYMPHOMA CELLS UNDER TARGETED REGULATION OF FOXO3 BY miR-155: miR-155, FOXO3, B-cell lymphoma, proliferation, apoptosis, clinical characteristics - Zheng, Xiaoqiang; Rui, Hongbing; Liu, Ying; Dong, Jinfeng (Mediterranean Journal of Hematology and Infectious Diseases, 2020)
This study aimed to explore the proliferation and apoptosis of B-cell lymphoma cells under targeted regulation of FOXO3 by miR-155. We analyzed the differences between B-cell lymphoma cells and B lymphocytes in expressions of miR-155 and FOXO3, explored the effects of miR-155 on proliferation and apoptosis of B-cell lymphoma cells, and relevant mechanisms, and also analyzed the relationship between expressions of miR-155 and FOXO3 in 42 patients with diffuse large B-cell lymphoma (DLBCL) and clinical characteristics of them. B-cell lymphoma cells showed a higher expression of miR-155 and a low expression of FOXO3 than B lymphocytes (both P<0.05). B-cell lymphoma cells transfected with miR-155-inhibitor showed significantly decreased expression of miR-155, significantly weakened cell proliferation ability and increased cell apoptosis rate (all P<0.05), and they also showed up-regulated expression of FOXO3 (P<0.05). Dual luciferase reporter assay revealed that there were targeted binding sites between miR-155 and FOXO3. Compared with B-cell lymphoma cells transfected with miR-155-inhibitor alone, those with co-transfection showed lower expression of FOXO3, higher proliferation and lower cell apoptosis rate (all P<0.05). The expression of miR-155 in DLBCL tissues was higher than that in tumor-adjacent tissues (P<0.05), and the expressions of miR-155 and FOXO3 were closely related to the international prognostic index (IPI) and the 5-year prognosis and survival of the patients (P<0.05). miR-155 can promote the proliferation of B-cell lymphoma cells and suppress apoptosis of them by targeted inhibiting FOXO3, and both over-expression of miR-155 and low expression of FOXO3 are related to poor prognosis of DLBCL patients.